2000
DOI: 10.1093/ps/79.3.426
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of turkey sperm to a synthetic peptide before insemination increases fertility

Abstract: Effects on fertility and hatch of eggs laid by hens inseminated with sperm exposed to a synthetic peptide were studied. Pooled semen from 40 randomly selected toms was split and held in vitro for 0 or 24 h before use. Just before insemination, sperm (at 8.33x10(9) sperm/mL) were exposed for 5 min to 0.0, 0.05, 0.25, or 0.50 microM peptide. Hens (28 per group) were inseminated within less than 30 min with 250x10(6) in 30 microL. Two inseminations 24 h before onset of lay were followed by weekly inseminations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Exposure of frozen thawed bull (Amann et al, 1999b) or rooster (Gill et al, 1999) sperm increased pregnancy rate or number of chicks hatched. Exposure of fresh turkey sperm to peptide S12-Ox increased poult production (Gill et al, 2000).…”
Section: Is the Upsebp System Important?mentioning
confidence: 95%
See 1 more Smart Citation
“…Exposure of frozen thawed bull (Amann et al, 1999b) or rooster (Gill et al, 1999) sperm increased pregnancy rate or number of chicks hatched. Exposure of fresh turkey sperm to peptide S12-Ox increased poult production (Gill et al, 2000).…”
Section: Is the Upsebp System Important?mentioning
confidence: 95%
“…We concluded that the intervening sequence between saposins A and B (Figure 1) and UPSEBP were similar and had similar biological activity; namely, increasing egg binding and fertility of rooster sperm. An abstract (Hammerstedt et al, 1997) presented early data, but 4 reports on bioactivity of the synthetic sequence (Amann et al, 1999a(Amann et al, , 1999b(Amann et al, , 1999cGill et al, 2000) bypassed the biological underpinning and path to the sequence used. This biological information is provided herein.…”
mentioning
confidence: 99%
“…O teste também tem sido usado para avaliar se a versão sintética (FertPlus®) de um fragmento da prosaposina, presente no plasma seminal, e envolvido na ligação dos espermatozóides à membrana perivitelina de aves, aumentaria a ligação e a fertilidade dos espermatozóides de touros , cachaços , perus (Gill et al, 1999a) e homens (Amann et al, , 1999c.…”
Section: Boar Semen Fertility Evaluated By a Sperm-binding Assay To Aunclassified
“…In addition, ef®ciency of IVF differs with mouse strain (Tada et al, 1990;Songsasen and Liebo, 1997) for unknown reasons. Recent reports (Barbato et al, 1998;Amann et al, 1999a, b, c;Gill et al, 1999Gill et al, , 2000Amann and Gill, 2000), testing a variety of avian and mammalian species describe: (a) an in vitro assay capable of distinguishing differences in sperm±ovum binding between individual males (and strains); and (b) the ability of exogenous peptide to alter fertilization rate. Barbato et al (1998) established the mouse sperm could bind to the test matrix, but provided neither an analysis of any stain-to-strain differences nor any evidence that extent of binding was related to fertilization potential.…”
Section: Introductionmentioning
confidence: 99%